Family Support Required to Increase Compliance of Medical Control of Patients with Cancers - Nurul Ramadhani Yaner; Tintin Sukartini; Kristiawati Kristiawati; M Ruli Maulana (Universitas Airlangga, 2019)
Introduction: Long and burdening therapeutic treatments of patients with cancers require social support in order to encourage patient’s medical compliance. Family support helps patients remain positive during their treatments so that they can develop physical and psychological fulfillment. This research identifies the correlation between family’s support and the rate of compliance of medical control of patients with cancer.Methods: The design was cross-sectional. The population was 60 patients with cancers who were undertaking treatment and 36 respondents were drawn by using a consecutive sampling technique. The independent variable is family support, while the dependent variable is the rate of compliance of patients with cancers in maintaining their medical control. The data was collected using questionnaires adopted from MMAS-8 (Medication Morisky Adherence Scale) and analyzed by using Chi Square with a significance rate of α ≤ 0.05.Results: The results indicated that the correlation between family’s support and the rate of medical compliance resulted in p=0.006.Conclusion: Supportive family support is very important in the successful treatment of cancer patients, because the family is closest to the patient, they live together, and also they have the opportunity to meet the needs of cancer patients.